2017
DOI: 10.15226/2381-2907/3/2/00129
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Infectious Bursal Disease in Backyard Chickens of Six Districts of North Shewa Zones of Oromia and Amhara Regions, Ethiopia

Abstract: SOJ Veterinary Sciences Open Access Research Articlebegin to walk at a faster pace, the limbs begin to impact with the ground and in so doing behave elastically [5]. Clearly, there is then an inverse relation between limb stiffness and an ability to convert potential energy into kinetic energy thus stiffness decreases as speed increases.In the trot, the body's center of mass behaves differently. Rather than being raised in the first half of the stance phase, it is lowered and the body moves as a wave, often wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…This finding in agreement with previous studies reported by Bedaso et al. ( 2017 ), Degefa et al. ( 2012 ), Jenbreie et al.…”
Section: Discussionsupporting
confidence: 94%
“…This finding in agreement with previous studies reported by Bedaso et al. ( 2017 ), Degefa et al. ( 2012 ), Jenbreie et al.…”
Section: Discussionsupporting
confidence: 94%
“…Location-wise, Fulbaria Upazila had the highest seropositivity (88.8%) of IBDV antibodies, whereas Trishal Upazila had the lowest (70.0%); however, no significant variations among the selected Upazilas of the Mymensingh district were noted. Female chickens had a significantly higher seroprevalence rate of IBDV antibodies than males, which is consistent with previous global studies [10,35,39,40]. Physiological and immunological variations between the sexes may support our findings [41].…”
Section: Discussionsupporting
confidence: 93%
“…Backyard chickens are extremely sensitive to infectious viral diseases owing to their wide access to and direct contact with wild birds [ 9 ]. Furthermore, the establishment of large-scale poultry (exotic) farms in rural areas can increase the risk of contagious viral diseases spreading to conventionally handled chickens [ 10 ]. Infectious bursal disease (IBD), the second most common viral disease in poultry, causes enormous economic losses, and thus has a negative influence on the poultry sector [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%